Mechanics of Arboreal Locomotion in Swinhoe’s Striped Squirrels: A Potential Model for Early Euarchontoglires - Wölfer, Jan; Aschenbach, Tina; Michel, Jenny; Nyakatura, John A. (Frontiers in Ecology and Evolution, 2021)
Differences between arboreal and terrestrial supports likely pose less contrasting functional demands on the locomotor system at a small body size. For arboreal mammals of small body size, asymmetrical gaits have been demonstrated to be advantageous to increase dynamic stability. Many of the extant arboreal squirrel-related rodents display a small body size, claws on all digits, and limited prehensility, a combination that was proposed to have characterized the earliest Euarchontoglires. Thus, motion analysis of such a modern analog could shed light onto the early locomotor evolution of eurarchontoglirans. In this study, we investigated how Swinhoe’s striped squirrels (Tamiops swinhoei; Scuiromorpha) adjust their locomotion when faced with different orientations on broad supports and simulated small branches. We simultaneously recorded high-Hz videos (501 trials) and support reaction forces (451 trials) of squirrels running on two types of instrumented trackways installed at either a 45° incline (we recorded locomotion on inclines and declines) or with a horizontal orientation. The striped squirrels almost exclusively used asymmetric gaits with a preference for full bounds. Locomotion on simulated branches did not differ substantially from locomotion on the flat trackway. We interpreted several of the quantified adjustments on declines and inclines (in comparison to horizontal supports) as mechanisms to increase stability (e.g. by minimizing toppling moments) and as adjustments to the differential loading of fore- and hind limbs on inclined supports. Our data, in addition to published comparative data and similarities to the locomotion of other small arboreal rodents, tree shrews, and primates as well as a likely small body size at the crown-group node of Euarchontoglires, render a preference for asymmetric gaits in early members of the clade plausible. This contributes to our understanding of the ancestral lifestyle of this mammalian ‘superclade’.